Госзаказ как инструмент инновационного развития предприятий, выпускающих электротранспорт (Путеводитель предпринимателя)
The current state of the enterprises of electric transport in Russia is considered, necessity of use of innovations in manufacturing of electric transport, as a way of increase of competitiveness of the domestic enterprises is shown. Use of the state order in the form of competition for purchases of hi-tech production, and also introduction of system of controlling.